Spatiotemporal heterogeneity management: Optimizing the critical role of ecosystem services in achieving Sustainable Development Goals - Lingli Zuo; Guohua Liu; Junyan Zhao; Jiajia Li; Shuyuan Zheng; Xukun Su (Geography and Sustainability)
Ecosystems play a pivotal role in advancing Sustainable Development Goals (SDGs) by providing indispensable and resilient ecosystem services (ESs). However, the limited analysis of spatiotemporal heterogeneity often restricts the recognition of ESs’ roles in attaining SDGs and landscape planning. We selected 183 counties in the Sichuan Province as the study area and mapped 10 SDGs and 7 ESs from 2000 to 2020. We used correlation analysis, principal component analysis, Geographically and Temporally Weighted Regression model, and self-organizing maps to reveal the spatiotemporal heterogeneity of the impacts of the bundle of ESs on the SDGs and to develop spatial planning and management strategies. The results showed that (1) SDGs were improved in all counties, with SDG 1 (No Poverty) and SDG 3 (Good Health and Well-being) exhibiting poor performance. Western Sichuan demonstrated stronger performance in environment-related SDGs in the Sichuan Province, while the Sichuan Basin showed better progress in socio-economic-related SDGs; (2) habitat quality, carbon sequestration, air pollution removal, and soil retention significantly influenced the development of 9 SDGs; (3) supporting, regulating, and provisioning service bundles have persistent and stable spatiotemporal heterogeneity effects on SDG1, SDG8, SDG11, SDG13, and SDG15. These findings substantiate the need for integrated management of multiple ESs and facilitate the regional achievement of SDGs in geographically intricate areas.